TGF‐β/BMP signaling pathway is involved in cerium‐promoted osteogenic differentiation of mesenchymal stem cells1. Issue 5 (14th March 2013) - Liu, Dan‐Dan; Zhang, Jin‐Chao; Zhang, Qun; Wang, Shu‐Xiang; Yang, Meng‐Su
Abstract The extensive applications of cerium (Ce) increased the chance of human exposure to Ce and its compounds. It was reported that Ce was mainly deposited in the bone after administration. However, the potential effect and mechanism of Ce on bone metabolism are not well understood. In this study, we investigated the cellular effects of Ce on the differentiation of mesenchymal stem cells (MSCs) and the associated molecular mechanisms. The results indicated that Ce promoted the osteogenic differentiation and inhibited the adipogenic differentiation of MSCs at cell level. Genes involved in transforming growth factor‐β/bone morphogenetic proteins (TGF‐β/BMP) signaling pathway were significantly changed when the MSCs were exposed to 0.0001 µM Ce by RT2Profiler™ PCR Array analysis. The expression of genes and proteins related to pathways, osteogenic, and adipogenic biomarkers of MSCs upon interaction with Ce was further confirmed by quantitative real‐time reverse transcriptase polymerase chain reaction (Q‐PCR) and Western blot analysis. The results suggest that Ce exerts the effects by interacting with bone morphogenetic protein receptor (BMPR) and activates TGF‐β/BMP signaling pathway, leads to the up‐regulation of the osteogenic master transcription factor, runt‐related transcription factor 2 (Runx 2), and the down‐regulation of the adipocytic master transcription factor, peroxisome proliferator‐activated receptor gamma 2 (PPARγ2). Runx2, which subsequently up‐regulates osteoblast (OB) marker genes collagen I (Col I) and BMP2 at early stages, alkaline phosphatase (ALP), and osteocalcin (OCN) at later stages of differentiation, thus driving MSCs to differentiate into OBs. The results provide novel evidence to elucidate the mechanisms of bone metabolism by Ce. J. Cell. Biochem. 114: 1105–1114, 2013. © 2012 Wiley Periodicals, Inc.